Drug utilization review of antipsychotic agents for inpatient treatment of schizophrenia in a tertiary government hospital - Malate, Jameca Mae M.; Salvan, Maria Rosewynn Anne R.; Sarabillo, Mara Angeli V.,​​ (2017)
Among the most common mental illnesses afflicting Filipinos, schizophrenia is the leading condition for which patients seek consultation and treatment. Medications typically used for this condition are antipsychotics, which are associated with multiple adverse effects, interactions and contraindications that complicate treatment. The objective of this study was to evaluate the drug utilization of antipsychotic drugs for the treatment of schizophrenia among inpatients in a tertiary government hospital, in terms of demographics, drug therapy problems, and compliance with the local treatment guidelines released by the National Center for Mental Health (2011). For this purpose, review of patient medical charts was done to gather the data necessary to accomplish the set objectives. Descriptive statistics were used to analyze the data.